The Effect of ZSM-5 Zeolite and Dolomite Catalysts on the Performance of Plastic Waste Pyrolysis - Tampubolon, Adam Jordan; Gamayel, Adhes; Zaenudin, Mohamad (Journal of Global Engineering Research and Science, 2023)
The increasing volume of waste in Indonesia, particularly plastic waste, has led to significant environmental challenges due to its continuous accumulation. Pyrolysis offers a sustainable alternative to conventional disposal methods, such as landfilling and incineration, which are known to contribute to pollution. Pyrolysis is a thermochemical decomposition process carried out in an oxygen-deficient environment, converting plastic waste into valuable products, including gas, oil, and char. These products have various applications: the gas can be used as a fuel, the oil as a liquid fuel, and the char as a solid fuel. This study investigates the pyrolysis of three types of plastic feedstocks: high-density polyethylene (HDPE), polypropylene (PP), and a 50:50 mixture of HDPE and PP. The catalysts employed were ZSM-5 zeolite, dolomite, and a mixed catalyst comprising ZSM-5 zeolite and dolomite, with a catalyst-to-feedstock ratio of 0.2:1. The results revealed that the highest oil yields were achieved using the ZSM-5 zeolite catalyst, producing 243 ml from HDPE, 370 ml from PP, and 380 ml from the HDPE-PP mixture. Conversely, the dolomite catalyst yielded the lowest oil production, with 82 ml from HDPE, 20 ml from PP, and 282 ml from the HDPE-PP mixture. Additionally, the ZSM-5 zeolite catalyst demonstrated a consistent increase in the oil production rate every 10 minutes across all feedstocks. These findings highlight the effectiveness of ZSM-5 zeolite in enhancing oil yield during pyrolysis, offering a viable pathway for converting plastic waste into valuable energy resources.